If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x(x + -3) = 4x + -3 Reorder the terms: -2x(-3 + x) = 4x + -3 (-3 * -2x + x * -2x) = 4x + -3 (6x + -2x2) = 4x + -3 Reorder the terms: 6x + -2x2 = -3 + 4x Solving 6x + -2x2 = -3 + 4x Solving for variable 'x'. Reorder the terms: 3 + 6x + -4x + -2x2 = -3 + 4x + 3 + -4x Combine like terms: 6x + -4x = 2x 3 + 2x + -2x2 = -3 + 4x + 3 + -4x Reorder the terms: 3 + 2x + -2x2 = -3 + 3 + 4x + -4x Combine like terms: -3 + 3 = 0 3 + 2x + -2x2 = 0 + 4x + -4x 3 + 2x + -2x2 = 4x + -4x Combine like terms: 4x + -4x = 0 3 + 2x + -2x2 = 0 Begin completing the square. Divide all terms by -2 the coefficient of the squared term: Divide each side by '-2'. -1.5 + -1x + x2 = 0 Move the constant term to the right: Add '1.5' to each side of the equation. -1.5 + -1x + 1.5 + x2 = 0 + 1.5 Reorder the terms: -1.5 + 1.5 + -1x + x2 = 0 + 1.5 Combine like terms: -1.5 + 1.5 = 0.0 0.0 + -1x + x2 = 0 + 1.5 -1x + x2 = 0 + 1.5 Combine like terms: 0 + 1.5 = 1.5 -1x + x2 = 1.5 The x term is -1x. Take half its coefficient (-0.5). Square it (0.25) and add it to both sides. Add '0.25' to each side of the equation. -1x + 0.25 + x2 = 1.5 + 0.25 Reorder the terms: 0.25 + -1x + x2 = 1.5 + 0.25 Combine like terms: 1.5 + 0.25 = 1.75 0.25 + -1x + x2 = 1.75 Factor a perfect square on the left side: (x + -0.5)(x + -0.5) = 1.75 Calculate the square root of the right side: 1.322875656 Break this problem into two subproblems by setting (x + -0.5) equal to 1.322875656 and -1.322875656.Subproblem 1
x + -0.5 = 1.322875656 Simplifying x + -0.5 = 1.322875656 Reorder the terms: -0.5 + x = 1.322875656 Solving -0.5 + x = 1.322875656 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.5' to each side of the equation. -0.5 + 0.5 + x = 1.322875656 + 0.5 Combine like terms: -0.5 + 0.5 = 0.0 0.0 + x = 1.322875656 + 0.5 x = 1.322875656 + 0.5 Combine like terms: 1.322875656 + 0.5 = 1.822875656 x = 1.822875656 Simplifying x = 1.822875656Subproblem 2
x + -0.5 = -1.322875656 Simplifying x + -0.5 = -1.322875656 Reorder the terms: -0.5 + x = -1.322875656 Solving -0.5 + x = -1.322875656 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.5' to each side of the equation. -0.5 + 0.5 + x = -1.322875656 + 0.5 Combine like terms: -0.5 + 0.5 = 0.0 0.0 + x = -1.322875656 + 0.5 x = -1.322875656 + 0.5 Combine like terms: -1.322875656 + 0.5 = -0.822875656 x = -0.822875656 Simplifying x = -0.822875656Solution
The solution to the problem is based on the solutions from the subproblems. x = {1.822875656, -0.822875656}
| (12r+12)=(24r-24) | | 3pi-(-12pi)= | | -45*(-1/5) | | 3pie-(-12pie)= | | x+1={4x} | | 5x-6=2(x+1)+1 | | (x/20)=-6 | | 1-5n=5+3n | | 7u^2-28m^2=0 | | 3/8r=36 | | -8/9x=24 | | x/7+1.3=2.1 | | 1/13a=2 | | -5-(6-2p)= | | 28x^4-3x^2-1=0 | | X-0.05X=8000 | | 8000=X-(X*0.05) | | -6x+2[5(x+1)+8]=38 | | -3+9x=24 | | 4x-5=-29 | | 3p+5=-7p-11 | | -3p+5=-7-11 | | -x+5*7=3*5 | | 2x-5*7=3*5 | | 6r-22=-54+2r | | 2x-7*5=3*5 | | 7x-11=-65+x | | 3x+2(x-l)+5=-4(X+2)-2x | | 2+3x=-5 | | 5*7-2x=3*5 | | X^3-7X^2-9X+63=0 | | 5*7=3*5 |